2014
DOI: 10.1002/aic.14606
|View full text |Cite
|
Sign up to set email alerts
|

UNIFAC model for ionic liquid‐CO (H2) systems: An experimental and modeling study on gas solubility

Abstract: in Wiley Online Library (wileyonlinelibrary.com)The universal quasichemical functional-group activity coefficients (UNIFAC) model for ionic liquids (ILs) has become notably popular because of its simplicity and availability via modern process simulation softwares. In this work, new group binary interaction parameters (a mn and a nm ) between CO (H 2 ) and IL groups were obtained by correlating the solubility data in pure ILs at high temperatures (above 273.2 K) collected from the literature. the solubility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 71 publications
(100 reference statements)
1
56
0
Order By: Relevance
“…The temperature of the still was controlled by electric heating elements with an uncertainty of ± 0.1 K, and the system pressure was measured by a pressure gauge with a range of 0–20.00 MPa and an uncertainty of ± 0.01 MPa. The details of apparatus and procedure have been described in our previous publications …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature of the still was controlled by electric heating elements with an uncertainty of ± 0.1 K, and the system pressure was measured by a pressure gauge with a range of 0–20.00 MPa and an uncertainty of ± 0.01 MPa. The details of apparatus and procedure have been described in our previous publications …”
Section: Methodsmentioning
confidence: 99%
“…The details of apparatus and procedure have been described in our previous publications. 22,23 Computational Details…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the IL was decomposed into several functional groups in a similar way as proposed by Lei et al [31][32][33][34], Kim et al [35,36], Breure et al [37]. Meanwhile, the benzene molecule was decomposed as six ACH groups, whereas thiophene and NMP were each treated as one separate group.…”
Section: Extension Of the Unifac Parameter Matrixmentioning
confidence: 96%
“…The UNIFAC model 32,33 and COSMO-RS model 34 are the models that are most widely used to describe phase equilibria in systems containing ionic liquids, and they are often applied to systems that lack phase equilibrium data. Lei et al 35,36 predicted the solubility of CO 2 and CO(H 2 ) in ILs using the UNIFAC model, and they obtained the interaction parameters for CO 2 , CO (H 2 ) and IL groups by correlating the model data with experimental data. Zhang et al 37 reported the predicted selectivity of CO 2 /CH 4…”
Section: The Densities and Viscosities Of [Bmim][pf 6 ] [Bmim][tf 2 mentioning
confidence: 99%